Vitamin B6 Prevents Endothelial Dysfunction, Insulin Resistance, and Hepatic Lipid Accumulation in Apoe−/− Mice Fed with High-Fat Diet - Zhan Liu; Peng Li; Zhi-Hong Zhao; Yu Zhang; Zhi-Min Ma; Shuang-Xi Wang (Journal of Diabetes Research)
Backgrounds. VitB6 deficiency has been associated with a number of adverse health effects. However, the effects of VitB6 in metabolic syndrome are poorly understood. Methods. VitB6 (50 mg/kg/day) was given to Apoe-/- mice with hkdigh-fat diet (HFD) for 8 weeks. Endothelial dysfunction, insulin resistance, and hepatic lipid contents were determined. Results. VitB6 administration remarkably increased acetylcholine-induced endothelium-dependent relaxation and decreased random blood glucose level in Apoe-/- mice fed with HFD. In addition, VitB6 improved the tolerance of glucose and insulin, normalized the histopathology of liver, and reduced hepatic lipid accumulation but did not affect the liver functions. Clinical and biochemical analysis indicated that the levels of VitB6 were decreased in patients with fatty liver. Conclusions. Vitamin B6 prevents endothelial dysfunction, insulin resistance, and hepatic lipid accumulation in Apoe-/- mice fed with HFD. Supplementation of VitB6 should be considered to prevent metabolic syndrome.